Phylogenomics of polyploid Fothergilla (Hamamelidaceae) by RAD‐tag based GBS—insights into species origin and effects of software pipelines. Issue 5 (9th September 2015) - Qi, Zhe‐Chen; Yu, Yi; Liu, Xiang; Pais, Andrew; Ranney, Thomas; Whetten, Ross; Xiang, Qiu‐Yun (Jenny); Wen, Jun; Liu, Jianquan; Ge, Song; Xiang, Qiu‐Yun (Jenny); Zimmer, Elizabeth A.
Abstract Fothergilla (Hamamelidaceae) consists of Fothergilla gardenii (4x) from the coastal plains of the southeastern USA, F. major (6x) from the piedmont and mountains of the same region, and a few allopatric diploid populations of unknown taxonomic status. The objective of this study was to explore the relationships of the polyploid species with the diploid plants. Genotyping by sequencing (GBS) was applied to generate genome‐wide molecular markers for phylogenetic and genetic structure analyses of 36 accessions of Fothergilla. Sanger sequencing of three plastid and one nuclear regions provided data for comparison with GBS‐based results. Phylogenetic outcomes were compared using data from different sequencing runs and different software workflows. The different data sets showed substantial differences in inferred phylogenies, but all supported a genetically distinct 6xF. major and two lineages of the diploid populations closely associated with the 4xF. gardenii. We hypothesize that the 4xF. gardenii originated through hybridization between the Gulf coastal 2x and an extinct (or undiscovered) 2x lineage, followed by backcrosses to the Atlantic coastal 2x before chromosome doubling, and the 6xF. major also originated from the "extinct" 2x lineage. Alternative scenarios are possible but are not as well supported. The origins and divergence of the polyploid species likely occurred during the Pleistocene cycles of glaciation, although fossil evidence indicates the genus might have existed for a much longer time with a wider past distribution. Our study demonstrates the power of combining GBS data with Sanger sequencing in reconstructing the evolutionary network of polyploid lineages.